INTEGRATING DESCRIPTIVE GEOMETRY WITH COMPUTATIONAL MODELING: A COGNITIVE AND PEDAGOGICAL FRAMEWORK FOR 21ST CENTURY TECHNICAL VISUALIZATION - Yusubjonov Jonibek Farkhod oglu (Bright Mind Publishing, 2025)
In the evolving landscape of technical education and engineering practice, the intersection between classical descriptive geometry and contemporary computational modeling represents both a challenge and an opportunity. This paper explores the pedagogical and conceptual integration of descriptive geometry with algorithmic and parametric modeling platforms such as CAD, BIM, and scripting environments. By analyzing the cognitive transitions that learners experience when moving from static geometric constructions to dynamic parametric models, the study proposes a unified framework that retains the foundational principles of descriptive geometry while enhancing its relevance in digital environments. Drawing on multidisciplinary sources—ranging from visual-spatial cognition studies to curriculum reforms in architecture and engineering schools—the paper argues that geometric literacy developed through descriptive geometry is essential for meaningful engagement with computational design tools. It presents empirical evidence from classroom interventions, comparative curriculum analyses, and expert interviews, revealing that students who are first trained in descriptive geometry demonstrate greater confidence and accuracy in developing complex 3D models, understanding spatial constraints, and resolving conflicts within multi-view systems. Furthermore, the research identifies critical points where algorithmic thinking and geometric reasoning converge, enabling educators to design cross-disciplinary learning experiences that prepare students for design automation, generative design, and advanced fabrication techniques. This paper concludes by offering practical recommendations for embedding descriptive geometry within modern modeling pedagogy, thereby cultivating a new generation of engineers and designers who are not only digitally fluent but geometrically literate.